Public Event: Confronting Internships: A Forum on Reforming Unpaid Work - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2015)
There will be a forum on unpaid internships to celebrate the publication of "Interrogating Internships: Unpaid Work, Creative Industries, and Higher Education"—a special issue of tripleC.The event will take place on November 4th, between 7:00 and 9:00 pm at room 420 in SFU's Morris J. Wosk Centre For Dialogue. Please see the attached poster for details.